Eficiência do uso de decocto de folhas de cajá (spondias mombin L.) In vitro e in vivo como antissépticos em gatos (felis catus) submetidos à ovariosalpingohisterectomia e orquiectomia - Dantas, Thalles D'Avila Pires Dutra (Universidade Federal Rural do Semi-Árido, 2018)
Studies show the use of Spondias mombin L. as antimicrobial, which shows that its extract may have antiseptic action. Being a natural product, easy to obtain and cheap, it is extremely important, especially to people who have little access to industrialized drugs, either because of the high price or because of logistical difficulties. Thus, the objective of this work was to evaluate the efficiency of cajá decoct as an antiseptic in surgical wounds of cats submitted to surgical sterilization. The animals used in the experiment were randomly selected and divided into three groups with 15 animals, where they were castrated and had their surgical wounds treated daily for 7 days. One group was treated with sterile distilled water (negative control), another with clorexidine 0.5% (positive control) and the test group with the decoct of cajá 100mg / ml. All the compounds remained for 10 minutes in contact with the surgical wound and after that time sterile swab was passed in the incision. Subsequently, they were taken to the laboratory for processing following the counting technique of aerobic mesophilic bacteria. The wounds were also evaluated for clinical aspects: hyperemia, edema, secretion, crusting and dehiscence. In the in vitro test, the bacteria isolated from the surgical wounds of cats of the negative control group were identified, using cytology and biochemical tests, and the sensitivity of these to the decoction by the well diffusion technique was tested. For the statistical analysis, the results of the microbiological analyzes were submitted to analysis of variance and the means were compared to each other by the Scott-Knott test, at a 5% probability level, using statistical software Sisvar®. The results showed that the group treated with the decoction of S. mobim leaves had a lower number of colony forming units than those treated with distilled water and higher than 0.5% of cloredixine. In the in vitro test, halos were formed for all the bacteria isolated and tested for the decoct of cajá. Regarding the clinical picture, there was little difference compared to the components used. In conclusion, the decoction of the leaves of Spondia mombim L. presented with a good antiseptic potential for surgically sterilized felines.
Monografia
Keywords: Plantas medicinais; Antimicrobiano; Produto natural; Medicinal plants; Antimicrobial; Natural product; CIENCIAS AGRARIAS::MEDICINA VETERINARIA